A Study of Trend Growth Rate of Confirmed Cases, Death Cases and Recovery Cases of Covid-19 in Union Territories of India - Haldhar Sharma, Dilip Kumar Sharma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The limit of COVID-19 cases in India is growing at a fast rate. The Mortal and localized authorities are having a solid dimension to create a route, study and anticipate the distribute of COVID-19 in India. The principal aim of this article is to gain a statistical leader for healthier savvy of COVID-19 spreading in India by soundly studying the reportable cases in the country 10 June 2020 to 7th August 2020 of union territories in India. Regression Analysis is implemented to measure the growth rate. The study revealed that India’s confirmed cases of COVID-19, death and recovery from covid-19 is increasing for the study period. The growth rate of recovery from COVID-19 is increasing, which clarify that the management of federal system of India is working effectively and efficiently.